Implementation of Balanced Scorecard in Indonesian Government Institutions: A Systematic Literature Review - Ari Erawan, I Gede (FIA UB, 2019)
In order to meet public pressure in improving government performance, many government institutions practice balanced scorecard as their performance management system. This paper describes how Indonesian government institutions implement balanced scorecard and its contribution toward their performance accountability. Delivering a systematic literature review of publications related to the implementation of balanced scorecard in public sector, it can be inferred that balanced scorecard helps the manager in Indonesian Ministry of Finance to fill the gap between strategic planning and strategic outcomes. Although, it has own disadvantages, balanced scorecard has proven on enhancing institution performance accountability based on evaluation conducted by Ministry of State Apparatus and Bureaucratic Reform. Its contribution is largely in performance planning indicator, since balanced scorecard focuses on strategic planning. Not only improves performance accountability, it is also founded that balanced scorecard supports the improvement of bureaucratic reform index. The essential factors in developing balanced scorecard implementation are explained as well. However, the differences compared to non-balanced scorecard organizations, has not been studied due to the limitation of the data, therefore future research is suggested.